Synergistic Antibiofilm Efficacy of Thymol and Piperine in Combination with Three Aminoglycoside Antibiotics against Klebsiella pneumoniae Biofilms - Borel Bisso Ndezo; Christian Ramsès Tokam Kuaté; Jean Paul Dzoyem (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Thymol and piperine are two naturally occurring bioactive compounds with several pharmacological activities. In this study, their antibiofilm potential either alone or in combination with three aminoglycoside antibiotics was evaluated against a biofilm of Klebsiella pneumoniae. Methods. Determination of antimicrobial susceptibility was performed using the broth microdilution method. Biofilm formation was evaluated by the microtiter plate method. Antibiofilm activity was determined using 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2H-tetrazolium-bromide (MTT) assay. The combination studies were performed by the checkerboard microdilution method. Results. The minimum biofilm inhibitory concentration (MBIC) of streptomycin was reduced by 16- to 64-fold when used in combination with thymol, while the MBIC of kanamycin was reduced by 4-fold when combined with piperine. The minimum biofilm eradication concentration (MBEC) values of streptomycin, amikacin, and kanamycin were, respectively, 16- to 128-fold, 4- to 128-fold, and 8- to 256-fold higher than the planktonic minimum inhibitory concentration (MIC). Thymol combined with streptomycin or kanamycin showed synergic effects against the preformed biofilm with 16- to 64-fold reduction in the minimum biofilm eradication concentration values of each antibiotic in combination. Piperine acted also synergically with kanamycin with an 8- to 16-fold reduction in the minimum biofilm eradication concentration values of kanamycin in combination. Conclusion. The association of thymol with antibiotics showed a strong synergistic effect both in the inhibition of biofilm formation and the destruction of the preformed biofilm of K. pneumoniae. This study suggests that a combination of thymol with streptomycin, amikacin, or kanamycin could be a promising alternative therapy to overcome the problem of K. pneumoniae biofilm-associated infections.